Fatores críticos na emulsificação por membranas : caracterização e avaliação do processo - Monteiro, Flávia Silva (2016)
The investigation of the critical factors involved in membrane emulsification (ME) using polymeric membranes was carried out. Two different techniques were applied (direct and premix ME with repetitive cycles) in order to obtain oil in water emulsions (O/W) using sunflower oil and lemon essential oil as a dispersed phase. Different flat sheet membranes (PVDF cut-off 800 kDa, MCE 0.22 µm and PES/PVP dporo ± 8μm) were used and both the applied pressure (ΔP) (1.4, 2.4 and 3.4 bar) and the continuous phase flow (100, 200 and 250 h-1) were varied. Emulsions were characterized for size and droplet size distribution (DSD), besides their stability. Both the morphology and hidrophilycity of the membranes are important to determine the droplets size distribution. Experimental conditions, such as applied pressure and continuous phase flow rate, also influence the size of the droplets, since they modify the balance of the forces acting on the pinned droplet. It was concluded that the membranes used were adequate for producing emulsions in the evaluated conditions, and that the ME technology has the potential to be used in the production of emulsions containing hydrophobic bioactive compounds, thus increasing the development of new products related to health and well-being in the food industry.